STRATEGY AND PRIORITIES FOR AGRICULTURE AND RURAL DEVELOPMENT IN ROMANIA - Cicea, Claudiu; Cvijanović, Drago; Subić, Jonel (Economics of Agriculture, 2007)
Agriculture remained a key sector of Romania in the framework of the pre accession period to the European Union. Thus, around of 41% of the employed population worked in the primary sector which represent approximately 14% of the Romanian GDP. The Copenhagen Summit Decisions, the Annual Report of EC of October 1999 on the Romanians Progress towards Accession as well as the general provisions of the EU Agenda 2000 Framework and the bilateral phase of the acquis screening reached the same conclusions as those of the National Strategy for the economical development of Romania presented to the European Union in March this year, meaning the need for Romania to create a functional market oriented economy, consistent with the principles, norms, mechanisms, institutions, and policies of European Union. The convergence foreseen in this respect is based on an evaluation of resources and opportunities of domestic and international context, and respond as laid down by the updated National Programme for the Adoption of the Acquis to the double requirement of finalisation of a market oriented economy and of preparation for the accession to the European Union, for using the historical chance offered by the decision of the European Council in Helsinki of December 1999 to open the negotiation of accession for Romania. In this given context, we will present in this paper the priority of harmonisation of the legislation concerning the SAPARD Programme measures, between 1999 and 2004.